Transformation, Politics and Implementation - Kirsch, Renate; Siehl, Elke; Stockmayer, Albrecht (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Working in environments characterised by a high degree of uncertainty, uncontrollability and unpredictability, development agents try to organise complex realities into manageable units. What principles influence the decision on adequate approaches and necessary steps?